2022
DOI: 10.1111/obr.13416
|View full text |Cite
|
Sign up to set email alerts
|

The impact of weight cycling on health outcomes in animal models: A systematic review and meta‐analysis

Abstract: The pattern of weight loss and regain, termed "weight cycling," is common in overweight individuals. It is unclear whether the well-established benefits of weight loss persist following weight regain or whether weight cycling is harmful. Human studies of weight cycling have conflicting results reflecting limitations of the observational designs of these studies. By controlling the macronutrient content of diets in animal studies, weight cycling can be studied in a highly controlled manner, thereby overcoming t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…For example, in one strain of mice, 40% CR led to greater weight loss than 20% CR, yet lifespan was longer in the mice with 20% CR [86]. Likewise, in one study, weight cycling generated by intermittent fasting increased lifespan without weight loss [125], although a recent meta‐analysis did not detect health benefits with weight cycling in rodents [126].…”
Section: Obesity Aging and Crmentioning
confidence: 99%
“…For example, in one strain of mice, 40% CR led to greater weight loss than 20% CR, yet lifespan was longer in the mice with 20% CR [86]. Likewise, in one study, weight cycling generated by intermittent fasting increased lifespan without weight loss [125], although a recent meta‐analysis did not detect health benefits with weight cycling in rodents [126].…”
Section: Obesity Aging and Crmentioning
confidence: 99%
“…After weight restoration, animals with WC had higher fasting glucose levels and impaired glucose tolerance. Our review of animal studies suggests that the health benefits of diet-induced weight loss are not sustained after the weight is regained and that WC leads to adverse metabolic outcomes [ 25 ]. In population studies, WC has also been a strong independent predictor of newly diagnosed diabetes.…”
Section: Systemic Effects On Wc: Metaflammation Of the Endocrine Syst...mentioning
confidence: 99%
“…The destruction of metabolic homeostasis due to excess energy may cause metaflammation, an adaptive response to relieve the anabolic pressure caused by obesity, and chronic low-grade inflammatory responses [ 20 ]. This inflammatory response may be permanent [ 21 ]. Consequently, this study aims to investigate the factors, sources, and molecular mechanisms of WC at three levels (systemic, tissue, and cellular) in terms of metaflammation during WC (Table 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…25 Weight cycling has a reputation for adverse physiological impacts (e.g., metabolic slowing or complications) with some empirical support. 26,27 However, systematic reviews have also suggested that weight cycling does not have a substantial negative metabolic impact, especially among persons with overweight or obesity. 28 Research in animal models suggests that weight-cycling may even be beneficial for longevity, as a clever study of weight-cycling mice showed that they outlived their rodent peers with sustained weight loss.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, 20%–35% of men and 20%–55% of women endorse weight cycling 24 , with adults endorsing progressively more frequent weight loss attempts than in prior years 25 . Weight cycling has a reputation for adverse physiological impacts (e.g., metabolic slowing or complications) with some empirical support 26,27 . However, systematic reviews have also suggested that weight cycling does not have a substantial negative metabolic impact, especially among persons with overweight or obesity 28 .…”
Section: Introductionmentioning
confidence: 99%